1993
DOI: 10.1002/bjs.1800800324
|View full text |Cite
|
Sign up to set email alerts
|

Repeat liver resection for recurrent colorectal metastases

Abstract: Sixteen patients underwent 18 repeat liver resections for recurrence of colorectal hepatic metastases that had been previously resected. Only minor liver resection had been undertaken at the first operation; three were palliative. The second operation was major hepatectomy in ten patients, minor resection in five and orthotopic liver transplantation in one. In one patient, lung metastases were resected before the second operation. One repeat hepatectomy was palliative. After partial liver resection, there were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
0
4

Year Published

1996
1996
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(49 citation statements)
references
References 27 publications
3
42
0
4
Order By: Relevance
“…14,3,6,7,[12][13][14][15][16][17][18][19][20][21]31 Of 457 patients undergoing second operations, 113 patients (25%) had reported complications. The most common complications reported were hemorrhage in 5%, significant pleural effusion in 5%, and infections in 10% of patients (including abscess formation in 5% and pneumonia in 2.4%).…”
Section: Resultsmentioning
confidence: 99%
“…14,3,6,7,[12][13][14][15][16][17][18][19][20][21]31 Of 457 patients undergoing second operations, 113 patients (25%) had reported complications. The most common complications reported were hemorrhage in 5%, significant pleural effusion in 5%, and infections in 10% of patients (including abscess formation in 5% and pneumonia in 2.4%).…”
Section: Resultsmentioning
confidence: 99%
“…Although hepatic resection has become the treatment of choice for patients with isolated liver metastases from colorectal cancer, more than 60% of the patients will develop recurrent disease after liver resection, [89][90][91][92] and half of these will initially recur only within the liver. 89,90,[93][94][95] As the safety and efficacy of liver resection has been increasingly accepted, repeat resections are also more commonly being performed. Although re-resections only account for 3% to 11% of all liver resections in experienced centers, [94][95][96][97] the number of repeat resections at major centers may be increasing.…”
Section: Results Of Liver Resection For Colorectal Metastasesmentioning
confidence: 99%
“…89,90,[93][94][95] As the safety and efficacy of liver resection has been increasingly accepted, repeat resections are also more commonly being performed. Although re-resections only account for 3% to 11% of all liver resections in experienced centers, [94][95][96][97] the number of repeat resections at major centers may be increasing. Bismuth et al 93 reported a significant increase in the percent of liver resections that are repeat resections at their institution from 6% (6 of 105) from 1983 to 1989 compared with 28% (49 of 177) from 1990 to 1994.…”
Section: Results Of Liver Resection For Colorectal Metastasesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, 65–78% of patients develop recurrence after initial hepatic resection [4,5,6,7,8], with 41–66% of these recurrences occurring in the remnant liver [5,7,8,9,10]. Nearly half of the recurrences (45%) occur within 6 months after initial hepatic resection and 88% within 2 years.…”
Section: Introductionmentioning
confidence: 99%